DIGITAL INTELLIGENCE: EDUCATION AS THE FOUNDATION FOR DIGITAL INTELLIGENCE - Agus Hidayat; Irwan Rachmiadji; Adil Barus; Al-Amin (Adisam Publisher, 2025)
Education is a fundamental pillar in the formation of digital intelligence, a crucial aspect in today's era of rapid technological transformation. When curriculum and teaching methods are integrated with information and communication technologies, students are equipped with the tools and knowledge to adapt, compete and innovate in an increasingly complex and connected society. This study uses the literature research method. The results show that the use of technology in education, in general, has a positive influence on increasing students' learning motivation, concept understanding, and problem-solving skills. Technology integration facilitates more interactive and personalized learning methods, encouraging deeper student engagement in the subject matter. However, the study also revealed that the success of technology integration is highly dependent on device accessibility and connectivity, teacher training and adequate infrastructure support. Inequality of access is one of the main barriers, necessitating specific intervention strategies to bridge the digital divide.